A yoga related aneurysm? An internal carotid artery aneurysm - Verónica Morillo-Jiménez; Elena Marin-Manzano; Marta Gutiérrez-Nistal; Jennifer Mondragón-Zamora; Juan D. Zafra-Angulo; Ãlvaro Fernández-Heredero (Revista Mexicana de Angiología, 2023)
Background: Aneurysms of the internal carotid artery (ICA) are a rare finding, only accounting for 0.4-4% of all peripheral aneurysm and 1% of all carotid diseases. Objective: To evaluate the clinical findings of a carotid aneurysm, considering the patient’s background. Methods: A 54-year-old woman intense yoga practitioner presented with 3 weeks development of a pulsatile mass on the right side of the neck. No history of intravenous catheters, traumatism, or local infections. Ultrasound images revealed a 1.6 cm patent saccular aneurysm ICA dependent. During surgery, visualization of the aneurysm was seen without sign of endothelial damage. Results: Patient underwent elective resection with primary repair and was discharged 2-day postoperatively. Follow-ups revealed complete resolution of the symptoms with intraoperative tissue samples coming back without abnormalities. Conclusions: It is of utmost importance to inquire into the patient’s background and perspective in being able to find an etiological case in rare findings.